2013
DOI: 10.1111/jch.12081
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects of Statins: A Meta‐Analysis of Prospective Controlled Studies

Abstract: In experimental studies, statins have been shown to lower blood pressure through increased nitric oxide bioavailability and improved arterial compliance. The clinical significance of this effect remains poorly documented. The authors performed a meta-analysis of the effect of statins on systolic blood pressure (SBP) and diastolic blood pressure (DBP) including prospective randomized, controlled trials of statin therapy. EMBASE and MEDLINE searches for studies in which patients were randomized to treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 53 publications
5
65
1
4
Order By: Relevance
“…15 A meta-analysis of antihypertensive effects of statins by Alexandros et al also showed a significant reduction in SBP and DBP in patients taking statins. 16 However in the present study, such results were not observed with respect to DBP in either group (Figure 2). At 16 weeks, comparison was done between Group-I and Group-II.…”
Section: Discussioncontrasting
confidence: 73%
“…15 A meta-analysis of antihypertensive effects of statins by Alexandros et al also showed a significant reduction in SBP and DBP in patients taking statins. 16 However in the present study, such results were not observed with respect to DBP in either group (Figure 2). At 16 weeks, comparison was done between Group-I and Group-II.…”
Section: Discussioncontrasting
confidence: 73%
“…Mean changes in SBP and DBP from baseline were then the key outcomes of in- The additive blood pressure lowering effect of statin therapy was considered to be the results of pleiotropic effect of statins. [4,15] There have been a growing number of evidence from both in vitro and animal studies that statins show pleiotropic effect such as increasing bioavailability of nitric oxide, improving endothelial-dependent vasodilation and reducing levels of endothelin-1, leading to reducing cardiovascular risk. [7,8,15,16] This phenomenon is deemed to be clinically important as hypertension and hyperlipidemia often co-exist within single patient and reducing cardiovascular risk would eventually lead to reduction in morbidity and mortality in patients.…”
Section: Discussionmentioning
confidence: 99%
“…По-видимому, это объяснимо уси-лением гипотензивного потенциала ста тинами [26]. Снижение АД было подтверждено данными СМАД, причем во всех группах исходной терапии отмечено положительное влияние на вариабельность АД фик-сированной комбинации лизиноприл+амлодипин+ розувастатин, что можно рассматривать как важную составляющую в коррекции SHATS синдрома (systemic hemodynamic atherothrombotic syndrome) [27].…”
Section: Discussionunclassified